2020
DOI: 10.1016/j.cjco.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

National Interhospital Transfer for Patients With Acute Cardiovascular Conditions

Abstract: Background Treatment of ST-elevation myocardial infarction (STEMI) in Canada is protocolized, and timely patient transfer can improve outcomes. Population-based processes of care in Canada for other cardiovascular conditions remain less clear. We aimed to describe the interhospital transfer of Canadian patients with acute cardiovascular disease. Methods We reviewed the Canadian Institute for Health Information Discharge Abstract Database for adult patients hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The various patterns of the imbalance in the baseline characteristics between the IHT group and non-IHT group among previous studies were also noticeable. Some studies reported that patients transferred with AMI were younger and had fewer comorbidities than those treated solely at the presenting hospital [ 19 , 20 ]; other studies had similar baseline characteristics [ 7 , 8 ]. In other studies, however, the transferred patients had a more pre-hospital cardiac arrest, a higher rate of cardiovascular risk factors, and Killip classes 3 or 4 on presentation [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The various patterns of the imbalance in the baseline characteristics between the IHT group and non-IHT group among previous studies were also noticeable. Some studies reported that patients transferred with AMI were younger and had fewer comorbidities than those treated solely at the presenting hospital [ 19 , 20 ]; other studies had similar baseline characteristics [ 7 , 8 ]. In other studies, however, the transferred patients had a more pre-hospital cardiac arrest, a higher rate of cardiovascular risk factors, and Killip classes 3 or 4 on presentation [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transferring patients between institutions, to facilitate advanced care may be necessary to achieve optimal clinical outcomes and salvage of life, but it also represents a period of heightened vulnerability for patients as well as physicians responsible for their care. IHT has been extensively studied, for numerous acute medical conditions such as trauma, acute ST-elevation myocardial infarction and stroke (14)(15)(16). However, the process of IHT for PE is less well understood.…”
Section: Introductionmentioning
confidence: 99%